Economic viability in the integrated crop-livestock system with nitrogen fertilization system and sward canopy heights - Elejalde, Denise Adelaide Gomes; Soares, André Brugnara; de Lima, José Donizetti; Missio, Regis Luis; Assmann, Tangriani Simioni; Tatto, Wilson Henrique; Deifeld, Felipe Luiz Chiamulera; Bortolli, Marcos Antônio de; Bernardon, Angela; Levinski-Huf, Flávia; Maccari, Marcieli; Barriga, Pablo Antonio Beltrán; et al. (Frontiers in Sustainable Food Systems, 2023)
Integrated crop-livestock systems (ICLS) are complex production strategies whose main components are soil, plant, and animal. Several studies addressed the interaction among them and conclude on the technical feasibility of these systems, but few studies assess their economic feasibility. The objective of this work was to analyze the economic feasibility of an ICLS, in which nitrogen was applied on the crop phase or onto the pasture phase, combined with two grazing intensities. The study was carried out on a private farm in the municipality of Abelardo Luz—SC, between October 2012 and April 2018. The experimental design was randomized blocks with three replications. The treatments were arranged in a 2x2 factorial scheme, with two sward heights (high and low) and two times of N-fertilization application, or on the cool-season pasture tillering phase either onto cash crop (200 kg of N ha−1 in a single dose). Crop implementation and maintenance costs were surveyed, followed by crop and livestock production calculations, zootechnical indices, and the revenue of each phase (pasture or grain crop) for the entire system. The cash flow analysis was carried out, generating economic indicators of the three dimensions of the expanded multi-index methodology (MMA) for the system and the treatments. In this study, pasture management with low sward canopy height provided the highest net gains per hectare and per hectare/year, regardless of the nitrogen application time. The use of the ICLS is economically viable, regardless of grazing intensities and nitrogen application times.